2005
DOI: 10.17221/3993-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental phytase on nutrient excretion and retention in broilers fed different cereal based diets

Abstract: A 21-day experiment with day-old broilers was conducted in order to assess the effect of phytase supplementation to different cereals-soybean meal based diets on nitrogen, calcium, total and phytate phosphorus excretion and retention. Diets were formulated to contain 4 different cereals (maize, wheat, triticale and barley), 2 levels of dietary calcium (0.6 and 1.0%) and 3 levels of supplemental phytase (0, 500 and 1 000 PU/kg). Nutrient intake, excretion and retention were determined in the first three days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…For K, Mg, Fe and Zn contents in the tibiae, the lowest values were characteristic for birds fed the diet supplemented with phytase III compared to those that consumed phytase I or II. Pintar et al (2005) observed a positive effect of phytase on Fe and Mg content in tibia, but, in contrast to the present work, no effect on Zn concentration. In yet another study (Shelton & Southern 2006), the removal of a trace mineral premix from a diet or phytase supplementation had no effect on Fe concentration in tibia.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For K, Mg, Fe and Zn contents in the tibiae, the lowest values were characteristic for birds fed the diet supplemented with phytase III compared to those that consumed phytase I or II. Pintar et al (2005) observed a positive effect of phytase on Fe and Mg content in tibia, but, in contrast to the present work, no effect on Zn concentration. In yet another study (Shelton & Southern 2006), the removal of a trace mineral premix from a diet or phytase supplementation had no effect on Fe concentration in tibia.…”
Section: Discussioncontrasting
confidence: 99%
“…However, some data do not show that phytase supplementation had a significant effect on bone mineralization in broilers (Perney et al 1993(Perney et al , Żyła et al 2000. In many studies, phytase supplementation affected macro and trace minerals content in tibia (Viveros et al 2002, Pintar et al 2005. Ravindran et al (1995) demonstrated that bone mineralization criteria are more sensitive indicators of P status in birds than growth criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the preceding papers we showed that: (i) magnitude of the beneficial effect of phytase supplementation on broiler performance varied between different cereals and calcium levels, (ii) supplemental phytase reduced the excretion of phytate phosphorus and increased its retention, magnitude of the effect depended on calcium dietary level, (iii) tibia ash content was not influenced by supplemental phytase (Pintar et al, 2004(Pintar et al, , 2005. In this paper effects on the mineral content in tibia are presented.…”
mentioning
confidence: 77%
“…From a limited number of investigations, the phytate-P proportion of total P excreted by poultry offered non-supplemented diets is probably less than anticipated. This proportion ranged from 0.28 to 0.38 in excreta from maize, wheat, triticale and barley-based broiler diets (Pintar et al, 2005) and, in turkeys, a range from 0.16 to 0.32 has been reported (Toor et al, 2005). McGrath et al (2005) reported that phytate-P represented 0.57 of total P in the excreta of broilers fed non-supplemented diets and 0.50 in those fed phytase-supplemented diets.…”
Section: Effect Of Exogenous Enzyme Supplementation On the Overall Pementioning
confidence: 98%